2012
DOI: 10.1523/jneurosci.5069-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Top-Down Integration of Prior Knowledge during Speech Perception

Abstract: A striking feature of human perception is that our subjective experience depends not only on sensory information from the environment but also on our prior knowledge or expectations. The precise mechanisms by which sensory information and prior knowledge are integrated remain unclear, with longstanding disagreement concerning whether integration is strictly feedforward or whether higherlevel knowledge influences sensory processing through feedback connections. Here we used concurrent EEG and MEG recordings to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
300
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(366 citation statements)
references
References 63 publications
60
300
6
Order By: Relevance
“…To assess the effect of prior knowledge on the immediate subjective clarity of degraded speech, participants completed a modified version of the clarity-rating task previously used in behavioral and MEG studies (Fig. 1B) (23,35). In this task, listeners are presented with spoken words varying in their amount of sensory detail (and therefore in their intrinsic intelligibility) and are asked to report their subjective experience of speech clarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of prior knowledge on the immediate subjective clarity of degraded speech, participants completed a modified version of the clarity-rating task previously used in behavioral and MEG studies (Fig. 1B) (23,35). In this task, listeners are presented with spoken words varying in their amount of sensory detail (and therefore in their intrinsic intelligibility) and are asked to report their subjective experience of speech clarity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this account makes two key experimental predictions, that (i) prior knowledge and perceptual learning should affect neural responses in the same brain network and (ii) the effect of prior knowledge observed online during perception should predict the magnitude of subsequent perceptual learning. However, because the brain systems supporting the influences of prior knowledge and perceptual learning typically have been observed separately (3,4,(21)(22)(23)(24)(25)(26), neither of these predictions has been tested successfully before.In this study, we obtained concurrent high-density EEG and magnetoencephalographic (MEG) recordings to compare the Significance Experience-dependent changes in sensory processing are critical for successful perception in dynamic and noisy environments. However, the neural and computational mechanisms supporting such changes have remained elusive.…”
mentioning
confidence: 99%
“…Previous studies have found that presenting a disambiguating stimulus (i.e., text or intact speech) at the same time (Wild et al., 2012a) or immediately after (Clos et al., 2014; Davis et al., 2005; Hervais‐Adelman et al., 2012; Sohoglu et al., 2012) the presentation of distorted speech increases comprehension of distorted speech. The current results and those of our previous studies (Hakonen et al., 2016; Tiitinen et al., 2012) extend these findings by showing that improvements in comprehension last for at least tens of seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, contradicting the hierarchical model of speech comprehension, activity in the primary auditory cortex has been shown to reflect speech intelligibility when speech is acoustically distorted (Wild et al., 2012b). Furthermore, speech comprehension specifically in acoustically adverse conditions has been associated with several brain areas including the left inferior frontal gyrus (Clos et al., 2014; Giraud et al., 2004; Hervais‐Adelman et al., 2012; Obleser & Kotz, 2010; Obleser, Wise, Dresner, & Scott, 2007; Shahin, Bishop, & Miller, 2009; Wild et al., 2012a), the anterior cingulate cortex (Erb, Henry, Eisner, & Obleser, 2012; Giraud et al., 2004), the anterior insula (Adank, 2012; Erb, Henry, Eisner, & Obleser, 2013; Giraud et al., 2004; Hervais‐Adelman et al., 2012; Shahin et al., 2009), the middle frontal gyrus (Giraud et al., 2004; Sohoglu et al., 2012), and the supplementary motor cortex (Adank, 2012; Erb et al., 2013; Hervais‐Adelman et al., 2012; Shahin et al., 2009). Subcortical brain structures may be involved in the adaptive plasticity that allows comprehension of even severely degraded speech (Guediche, Blumstein, Fiez, & Holt, 2014a; Guediche, Holt, Laurent, Lim, & Fiez, 2014b; Jääskeläinen et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Predictive coding is an optimal inference framework based on the idea that the brain internalizes forward models (how world events lead to sensory consequences), and that what travels from the sensory periphery to the brain are prediction errors (Rao & Ballard, 1999). The presence of predictive mechanisms in auditory and audio-visual speech processing has been shown experimentally (Bendixen, Scharinger, Strauß, & Obleser, 2014;Gagnepain, Henson, & Davis, 2012;Sohoglu, Peelle, Carlyon, & Davis, 2012;Van Wassenhove, 2013) and explored at the theoretical level (Yildiz, von Kriegstein, & Kiebel, 2013). The model we present involves predictive mechanisms in audio-visual speech synthesis and, unlike previous works (Bejjanki, Clayards, Knill, & Aslin, 2011;Magnotti & Beauchamp, 2014;Magnotti, Ma, & Beauchamp, 2013;Massaro, 1998;Omata & Mogi, 2008;Yildiz et al, 2013), takes into account the dynamic processing of both acoustic and visual information.…”
Section: Introductionmentioning
confidence: 99%